Morphophysiological characteristics of okra plants submitted to saline stress in soil with organic fertilizer - Sousa, Geocleber Gomes de; Mendonça, Andreza de Melo; Sales, Jonnathan Richeds da Silva; Silva Junior, Francisco Barroso da; Moraes, João Gutemberg Leite; Sousa, José Thomas Machado de (Comunicata Scientiae, 2020)
The excess of salts may compromise the growth and physiological functions of plants, but the use of bovine organic fertilizer can mitigate these effects. It was intended was to evaluate the saline stress in soil with and without bovine organic fertilizer on the initial growth, the accumulation of biomass and the gas exchanges of the okra culture. The test was conducted at the UNILAB’s experimental farm, in Piroás, in Redenção – CE city. The treatments were distributed in a completely randomized design with five replications, in a 5 x 2 factorial concerning five irrigation water salinity levels (1.0; 2.0; 3.0; 4.0 and 5.0 dS m-1), in the presence and absence of bovine organic fertilizer. Plant height, stem diameter, root length, a dry mass of shoot, photosynthesis, transpiration and stomatal conductance were evaluated. The bovine organic fertilizer promoted better means in initial growth and biomass in okra plants compared to the control treatment, thus showing efficiency in the attenuation of the salts present in irrigation water. The increase in the saline concentration of the irrigation water reduced the gas exchange (photosynthesis, stomatal conductance and transpiration) in okra plants. Nonetheless, in smaller proportions in the soil with the bovine organic fertilizer.